FEATURES OF THE INTESTINAL MICROBIOME FORMATION AND THE LEVEL OF INTESTINAL INFLAMMATORY RESPONSE IN NEWBORNS - Popov, Serhiy V.; Profatylo, Anastasiia O.; Turner, Mark A.; McDonnell, Euan; Gutiéerrez, Eva Caamañno; Evans, Anthony; Smiyan, Oleksandr I.; Bokova, Svitlana I. (Eastern Ukrainian Medical Journal, 2025)
Objectives. We aim to explore the relationship between the composition of the faecal bacterial flora and the level of faecal calprotectin (FC) in sequential assessments of healthy term newborns. Methods. The study was conducted thrice during the second, third, and fifth weeks of life. Culture method was used to identify the composition of intestinal microbiome indicators. FC levels were measured using an enzyme-linked immunosorbent assay. Mixed-effects linear modelling were applied to test for associations between calprotectin and various clinically relevant covariates/factors. Results. Thirty-two infants were studied. Levels of Bifidobacterium was for children two weeks old (mean, standard deviation) – 8.91±1.47 CFU/g, for three weeks old – 8.44±1.58 CFU/g and for five weeks old – 8.09±1.49 CFU/g and Lactobacilli number for two weeks old – 7.69±1.15 CFU/g was higher than for three weeks old – 7.13±1.45 CFU/g and for five weeks old – 6.75±1.87 CFU/g. Level of FC for two weeks old was 280.6±123.68 mg/l, for three weeks old – 195.3±115.5 mg/l and for five weeks old – 153.5±34.6 mg/l. FC decreased with time and was higher in the presence of colonisation with Bifidobacterium, Lactobacilli, E.coli, and Opportunistic/Conditional pathogens. Conclusions. The number of Bifidobacterium and Lactobacilli decreased during the neonatal period. FC also decreased but was higher in newborns colonised with Bifidobacterium, Lactobacilli, E.coli, and Opportunistic/Conditional pathogens, which apparently reflected stabilised composition of the microbiome and associated change in inflammatory processes.